Gambaran Pemnafaatan Lahan Basah (Wetland) pada Masa Jawa Kuna - Andri Restiyadi (Berkala Arkeologi Sangkhakala, 2008)
AbstractWetland have an important values as a system in cultural ecology. The used management of wetland have been known by archaeological remains since prehistoric era. In the Ancient Javanese era, many inscriptions explained that people in those era have used the wetland for example as an agriculture and exploited the animal for daily compsumtion, comodity, and ritual ceremony